The Necessity of Psychotherapy in the Practice of Physical Exercises: Array - Panfiloiu, Camelia; Aramă, George Laurențiu (Journal of Danubian Studies and Research, 2021)
Now a days it is important for the people to be aware of the importance of psychotherapy in practicing physical activity. Living in a world where the people are having more and more health problems because of obesity and the ignorance for self-care, due the fact that they are more involved in their jobs and family issues, the necessity of the practice of physical exercises it is mandatory. The best method to make the people understand the benefits of practicing physical activities is to participate at psychotherapy sessions which are very helpful to chance the mentality of the people regarding this necessity and to show them that taking care of their bodies represents a very healthy way to improve their state of mind. The fundamental aim of this study is to demonstrate that the psychotherapy and the practice of physical activities are 2 items that should be combined in the health programs in order to have the best results and also, one other purpose of this study, is to convince people that their health is more important than their jobs and if they manage to improve the process of self-care is going to help them to reduce the stress.